Success Factors Driving Intra-Organizational Knowledge Transfer - FUN, SWEE FONG (2004)
Knowledge transfer (KT) has become an important activity for an organization to sustain its effectiveness. By understanding the factors, it will help organizations to use knowledge transfer as a tool to create and distribute knowledge among their employees. Consequently, it will assist managers to implement strategies in boosting organizational success, and to sustain superior performance.